PERENCANAAN REKONSTRUKSI PERKERASAN LENTUR TAXIWAY CHARLIE DI BANDAR UDARA INTERNASIONAL JUWATA TARAKAN - Bambang Wasito; Wildan Hisyam Rafi Achmad; Ranatika Ranatika (Approach : Jurnal Teknologi Penerbangan, 2019)
Lombok International Airport is the premier second-class airport located in Tanak Awu, Pujut, Lombok Tengah, Nusa Tenggara Barat which functions to serve transportation services. Lombok International Airport has runway, apron, and two taxiways along with its drainage. The drainage system is needed to prevent puddles of rainwater in the runway, taxiway and apron that can obstruct the aircraft movement. However, looking at the existing condition of the Lombok International Airport’s trunk, it is necessary to conduct research about trunk reconstruction for the next ten years’ time. The research is begun by collecting data such as existing elevation, existing dimension, slope of existing trunk and rainfall data for the last five years. From these data, an analysis of the rainfall plan is carried out using gumbel distribution method. Furthermore, from the results of the analysis, it is obtained the daily maximum rainfall which is used to know the rainwater runoff debit. Re-planning the dimensions of Lombok International Airport’s trunk is carried out to accommodate rainwater runoff debit for the next ten years since the existing dimensions of the existing trunk cannot accommodate rainwater runoff debit for the next ten years. Therefore, it was obtained the design plan for the reconstruction of each segment with a length of 1,2 meters, width of 1,84 meters and height of 1,77 meters. Re-planning the dimensions of the trunk is in precast concrete.